The Prevalence of Nocturnal Enuresis among Iranian Children: A Systematic Review and Meta-Analysis - Mohammadi, Masoud; Vaisi Raiegani, Ali Akbar; Jalali, Rostam; Ghobadi, Akram; Salari, Nader (Urology Journal, 2019)
Purpose: Nocturnal enuresis is one of the most common diseases in children, which can affect their mental health. The aim of the present study is to determine the prevalence of nocturnal enuresis in Iranian children through systematic review and meta-analysis. Materials and Methods: The present study was conducted through systematic review and meta-analysis of studies during March 2000- July 2018. Articled related to the subject were reviewed by searching the Medline (PubMed), Scopus, ScienceDirect, SID, Magiran, Barakat, and Google Scholar databases where the heterogeneity of studies was investigated using I2 index. The data analysis was then carried out using Comprehensive Meta-Analysis software. Results: 15 articles with a sample size of 16614 individuals aged 3 to 18 years entered the meta-analysis process. The overall prevalence of nocturnal enuresis in children of Iran was 10.2% (95% CI: 7-14.8%). The highest and lowest prevalence of nocturnal enuresis was seen in children living in Tehran 28.5% (95% CI: 16.1% -45.4) and Tabriz 1.8% (95% CI: 1.2-2.8%), respectively. The findings of the present study revealed that the prevalence of nocturnal enuresis in children decreases with enlargement of the sample size. In addition, the prevalence of nocturnal enuresis grows with an increase in the years of research, which is statistically significant (P < 0.05). Conclusion: Considering the high prevalence of nocturnal enuresis in the current study, health policy makers need to raise the awareness of families by taking efficient and effective policies.